Development of a Battery Maintenance and Charging System with a LoRa-based Ethernet Network (Study Case PT. KAI DAOP 8 Surabaya, Gubeng Station) - Harsanti, Nella Abda Putri; Saptono, Rachmad; Yulianto, Ahmad Wilda (Jurnal Jaringan Telekomunikasi, 2024)
Gubeng Station under PT. KAI DAOP 8 Surabaya requires a backup power source, such as a backup battery as a replacement for the main battery, to ensure continuous operation of the station. So, regular maintenance is carried out for the backup battery by charging them. However, there is no monitoring system for battery charging because the internet access at a distance of ±37.92 meters via Ethernet and voltage data after charging has turned yellow making maintenance and monitoring of charging difficult. Therefore, this research aims to develop a battery charging monitoring system with a LoRa-based ethernet network. When testing this system by charging a 12 VDC 65 Ah battery, the system can monitor the voltage and charging current values using a voltage sensor and ACS712 recorded in real-time in the Android application with an ethernet-based LoRa module with a maximum distance between the sending and receiving devices of 97, 9 meters in non-LoS conditions. The system also succeeded in auto cut off and sent a notification in the application when charging was complete with a recorded voltage and current of 14.01 V -0.22 Amperes.